Polypyrrole-Coated Jute Substrate for Electromagnetic Shielding. Issue 1 (January 2015) - Khare, Shalu; Deogaonkar, Smita C.; Savadekar, Niranjan
In this study, electrically conductive polypropylene (PP) and jute nonwoven fabrics were synthesized by a chemical oxidative polymerization process using pyrrole as a monomer and iron chloride hexahydrate as an oxidant. After fabric production, electrical, morphological, and electromagnetic properties were determined. The deposition of polypyrrole (PPy) on nonwoven fabrics was confirmed by scanning electron microscopy (SEM) analysis. Electrical properties were evaluated as surface resistivity using two probe flat plate electrode systems. The electromagnetic interference shielding of PPy-coated fabrics (PP and jute nonwovens) and composites was measured as shielding effectiveness (SE) in the frequency range of 100 MHz to 1.5 GHz using the co-axial transmission line method.